Sales Promotion Produk Kopi Melalui Media Sosial Instagram - Diar Wardani; Aning Sofyan (Bandung Conference Series: Communication Management, 2023)
Abstract. Sales promotion is one aspect of the marketing mix that is dedicated to introducing new products to increase sales volume. Marlina Kopi is one of the business people in the cafe or commonly called a coffee shop who plays a role in sales promotion activities to sell the products they have. The purposes of this study are to find out the forms of sales promotion used in marketing coffee products through Instagram @marlinakopi social media. This study uses a qualitative method with a case study approach. The research subject chosen by the researcher was Marlina Kopi located in Lemahsugih, Majalengka Regency, West Java Province, by interviewing the owner, employees, and visitors of Marlina Kopi. Data collection techniques used include interviews, observations, and literature studies. The results of this study are Kedai Marlina Kopi uses sales promotion techniques which include installing locations on google maps, providing food menus and facilities that adapt to the target market, and providing discounts in the form of vouchers and holding events with prizes. The use of model portraits in Instagram content is done because it wants to show that Marlina Kopi can not only enjoy coffee but also has other service facilities such as qualified photo spots and can also be a location for wedding celebrations. So that the increase and addition of this facility is expected to increase interest and provide happiness for those who visit Marlina Kopi. Abstrak. Sales promotion merupakan salah satu aspek dari bauran pemasaran atau marketing mix yang didedikasikan untuk memperkenalkan produk baru guna meningkatkan volume penjualan. Marlina kopi adalah adalah salah satu pelaku bisnis dibidang café atau biasa disebut coffee shop yang berperan dalam kegiatan sales promotion untuk menjual produk yang mereka miliki. Tujuan dari penelitian ini adalah untuk mengetahui bentuk-bentuk sales promotion yang digunakan dalam memasarkan produk kopi melalui media sosial Instagram @marlinakopi. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus. Subjek penelitian yang dipilih oleh peneliti yakni Marlina Kopi yang bertempatan di Lemahsugih, Kabupaten Majalengka, Provinsi Jawa Barat, dengan mewawancarai owner, karyawan, dan pengunjung Marlina kopi. Teknik pengumpulan data yang dilakukan antara lain wawancara, observasi, dan studi literatur. Hasil dari penelitian ini adalah Kedai Marlina Kopi menggunakan teknik sales promotion yang meliputi pemasangan location di google maps, menyediakan menu makanan dan fasilitas yang menyesuaikan dengan target pasar, dan memberikan diskon dalam berupa voucher dan mengadakan event-event berhadiah. Penggunaan potret model didalam konten Instagram dilakukan karena ingin memperlihatkan bahwa Marlina Kopi tidak hanya bisa menikmati kopi namun juga memiliki fasilitas pelayanan lainnya seperti spot foto yang mumpuni dan juga dapat menjadi lokasi perayaan wedding. Sehingga peningkatan dan penambahan fasilitas ini diharapkan dapat menambah minat serta memberi kebahagiaan bagi yang berkunjung ke Marlina Kopi.